USING THINK PAIR AND SHARE TOWARD STUDENT’S READING SKILLS ON KURIKULUM MERDEKA BASED LEARNING - Bayu Gilang Sanjaya; Ali Akbarjono; Fera Zasrianita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The research used is quantitative with a quasi-experimental type. The population obtained from this research were class 10 students at SMA N 3. This research used a purposive sampling technique to determine two classes as samples, class 10 K consisting of 33 students as the control class and class 10 L consisting of 36 students as the class experiment. Based on the research results that have been tested, the researcher obtained an average pretest score for the control class with a value of 45.97 with a std error value of 2,964, while the average score for the experimental class was 55.00 with a std error value of 2840. Based on the pretest results, it can be seen that knowledge the basis of the experimental class is more than the control class. Furthermore, the average post-test score for the control class was 69.35 with a std error of 1,762, while the average post-test score for the experimental class was 76.03 with a std error of 1,413. Based on the results of the post-test that has been carried out, it can be concluded that after carrying out the treatment using the Think, pair, and share teaching model, significant changes were obtained based on the results of the average between the control and experimental classes adapting to the Merdeka curriculum at SMAN 3 Bengkulu City.